Hydration state of single cytochrome c monolayers on soft interfaces via neutron interferometry. - Kneller, L R (2001)
Yeast cytochrome c (YCC) can be covalently tethered to, and thereby vectorially oriented on, the soft surface of a mixed endgroup (e.g., -CH3/-SH = 6:1, or -OH/-SH = 6:1) organic self-assembled monolayer (SAM) chemisorbed on the surface of a silicon substrate utilizing a disulfide linkage between its unique surface cysteine residue and a thiol endgroup. Neutron reflectivities from such monolayers of YCC on Fe/Si or Fe/Au/Si multilayer substrates with H2O versus D2O hydrating the protein monolayer at 88% relative humidity for the nonpolar SAM (-CH3/-SH = 6:1 mixed endgroups) surface and 81% for the uncharged-polar SAM (-OH/-SH = 6:1mixed endgroups) surface were collected on the NG1 reflectometer at NIST. These data were analyzed using a new interferometric phasing method employing the neutron scattering contrast between the Si and Fe layers in a single reference multilayer structure and a constrained refinement approach utilizing the finite extent of the gradient of the profile structures for the systems. This provided the water distribution profiles for the two tethered protein monolayers consistent with their electron density profile determined previously via x-ray interferometry (Chupa et al., 1994).